(untitled) (Economics and region, 2021)
The article identifies the impact of foreign investment on the production of agricultural organic products in Ukraine. The development of organic production is quite relevant today due to a number of obvious environmental, economic and social benefits inherent in this field. The recent intensification of agriculture around the world has a negative impact not only on the environment, but also on the depletion of natural resources, without which agricultural production is impossible. Therefore, organic agriculture has environmental benefits, which have great potential to correct the previously mentioned negative trends, as well as reduce emissions of carbon dioxide, nitrous oxide and methane, which contribute to global warming. Organic farming also has significant health benefits. First, it reduces the risk of health loss for agricultural workers, as they are the most vulnerable to pesticides and other chemicals used in conventional production. Second, organic products are more beneficial to consumers by minimizing the health effects of toxic and persistent chemicals. Therefore, the global market for organic products is growing rapidly. Ukraine is only taking the first steps in forming and establishing a market for organic products, which is already well developed in other countries (including the EU).Trends in the development of organic production in the domestic market are considered. The study substantiates the conclusion that foreign investment is one of the effective tools for the development of organic agriculture and ensure its competitiveness. Today, due to their large scale, foreign investments have a significant impact on the state and functioning of the domestic market of organic products and contribute to the solution of development priorities. Foreign sources of investment cannot play the role of the main lever of economic growth, but if they are used wisely and rationally, even small incomes will help revive agricultural production and increase its efficiency, especially in the direction of organic production.